2020
DOI: 10.1111/eip.13089
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of complete blood count inflammatory markers in substance‐free acute psychotic disorder and substance‐induced psychosis

Abstract: Aim Recent studies showed a compare complete blood count (CBC) with its related measurements, including neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), and platelet to lymphocyte ratio, are a simple and affordable test for inflammatory markers. The aim of this controlled study is to compare CBC inflammatory markers in substance‐induced psychosis (SIP) and substance‐free acute psychotic disorder (SF‐APD) and to evaluate whether these CBC inflammation values can be used in diagnosis. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The differences between the two patient groups in most parameters were less noticeable, with WBC, monocyte, MLR and PLR not differing significantly. Our findings support earlier research showing that individuals with schizophrenia 31,32 and substance-induced psychotic disorder 33 had stronger inflammatory responses than the healthy control group, as seen by enhanced WBC, neutrophil, basophil, NLR and MLR. The results demonstrated that both of the patient groups were impacted by significant inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between the two patient groups in most parameters were less noticeable, with WBC, monocyte, MLR and PLR not differing significantly. Our findings support earlier research showing that individuals with schizophrenia 31,32 and substance-induced psychotic disorder 33 had stronger inflammatory responses than the healthy control group, as seen by enhanced WBC, neutrophil, basophil, NLR and MLR. The results demonstrated that both of the patient groups were impacted by significant inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results found the neutrophil count in patients with schizophrenia was higher and with lower lymphocyte count than the patients with methamphetamine‐induced psychotic disorder. This is consistent with a previous study, 33 which found higher NLR in substance‐free acute psychotic disorder and substance‐induced psychosis than controls as well as the group with substance‐free acute psychotic disorder had higher neutrophils and lower lymphocyte count than the group with substance‐induced psychosis. In addition, higher MLR in the two groups of patients was also observed in that study.…”
Section: Discussionmentioning
confidence: 99%